Overweight and obesity in public schools' adolescents from Fortaleza: an exploratory study - Marta Maria Coelho Damasceno; Ana Roberta Vilarouca da Silva; Hérica Cristina Alves de Vasconcelos; Márcio Flávio Moura de Araújo; Paulo César Almeida; Roberto Wagner Júnior Freire de Freitas (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
Nowadays overweight is a condition that prepares adolescents to several chronical diseases in the future. Thus, the objective was to find out overweight and obesity cases in public schools' adolescents from Fortaleza. 720 students between 14 and 19 years of age were investigated in the months of February and March, 2006, by means of a form application in which socio-demographic features, weight, height, Body Mass Rate (BMR) were recorded. Results highlighted that 65.8% were between 14-17 years old, 81% attended highschool, 59.3% belonged to the female gender and 12.9% had an above normal BMR. Out of these, 10.3% were overweight, 2.6% were obese, 7.6% belonged to the female gender and 8.4% were between 14-17 years old. Overweight/obesity predominance was higher in those with lower income, although a statistically significant association was not found (p=0.342). However, there was a significant association between BMR and age (p= 0.003). It was inferred that the raise of overweight cases among the investigated may be related to the adoption of a predisposing lifestyle. In this context, the nurse should implement intervention and prevention actions such as education in health and early detection of overweight cases.